2013
DOI: 10.1002/ajmg.a.36007
|View full text |Cite
|
Sign up to set email alerts
|

Autosomal dominant oculoauriculovertebral spectrum and 14q23.1 microduplication

Abstract: Oculoauriculovertebral spectrum (OAVS; OMIM 164210) is characterized by anomalies derived from an abnormal development of the first and second branchial arches, with marked inter and intra-familial phenotypic variability. Main clinical features are defects on aural, oral, mandibular, and vertebral development. Cardiac, pulmonary, renal, skeletal, and central nervous system anomalies have also been described. Most affected individuals are isolated cases in otherwise normal families. Autosomal dominant inheritan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 21 publications
(36 reference statements)
3
39
0
3
Order By: Relevance
“…Deletions of the 12p13.33 region, involving the WNT5B gene, were observed in some but not all patients with OAVS features 44 45. Partially overlapping microduplications on 14q23.1 were identified in two families with autosomal dominant OAVS;46 47 one of these families included two first-degree relatives with clinical features of OAVS and Branchio-oto-renal syndrome; hence, the region 14q23.1 might harbour candidate genes for OAVS and additional first and second pharyngeal arch developmental disorders. Anomalies in 22q have been frequently documented in patients with OAVS, particularly the 22qter deletion,51 22q11.2 deletions,52–54 the 22q11.1-q11.21 (Cat-eye) region,56 57 and a partial 22 trisomy (47,XX,+der(22)t(11;22)(q23;q11)), which duplicates the 22q11 region 66.…”
Section: Overview Of Oculo-auriculo-vertebral Spectrummentioning
confidence: 99%
“…Deletions of the 12p13.33 region, involving the WNT5B gene, were observed in some but not all patients with OAVS features 44 45. Partially overlapping microduplications on 14q23.1 were identified in two families with autosomal dominant OAVS;46 47 one of these families included two first-degree relatives with clinical features of OAVS and Branchio-oto-renal syndrome; hence, the region 14q23.1 might harbour candidate genes for OAVS and additional first and second pharyngeal arch developmental disorders. Anomalies in 22q have been frequently documented in patients with OAVS, particularly the 22qter deletion,51 22q11.2 deletions,52–54 the 22q11.1-q11.21 (Cat-eye) region,56 57 and a partial 22 trisomy (47,XX,+der(22)t(11;22)(q23;q11)), which duplicates the 22q11 region 66.…”
Section: Overview Of Oculo-auriculo-vertebral Spectrummentioning
confidence: 99%
“…Moreover, clinical studies have shown that, following careful history and clinical examination of the relatives of probands with OAVS, up to 45% of "unaffected" relatives do have minor OAVS manifestations [13]. Reports of familial cases following Mendelian inheritance [4,[14][15][16][17], as well as evidence for genetic linkage in two families [18,19], and the presence of OAVS features in patients with various chromosomal aberrations and genomic imbalances [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38], all suggest that some cases of OAVS have a genetic basis. Environmental causes have also been suggested, particularly twinning, assisted reproductive techniques and maternal pre-pregnancy diabetes [1,3].…”
Section: Introductionmentioning
confidence: 99%
“…6 Familial history suggestive of both autosomal recessive and dominant inheritance has been reported, and genes on chromosomes 5, 12, 14, and 22 have been implicated. [7][8][9][10] However, most cases of OAVS are sporadic and without a known etiology. Abnormal embryonic vascular supply, 11 hematomas, and drug use during the early phases of gestation have been reported to cause the disruption of mesodermal migration, leading to defective formation of bone and soft-tissue structures.…”
mentioning
confidence: 99%